2017
DOI: 10.1016/j.jaci.2016.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Broad spectrum antibiotic enrofloxacin modulates contact sensitivity through gut microbiota in a murine model

Abstract: Oral treatment with a broad spectrum antibiotic modifies gut microbiota composition and promotes anti-inflammatory response, suggesting that manipulation of gut microbiota can be a powerful tool to modulate the course of CS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 48 publications
4
38
1
Order By: Relevance
“…In line with the results from the current study, oral administration of broad-spectrum antibiotic cocktails is often reported to increase the relative abundance of CD4 + Treg cells in small intestine (Ivanov et al, 2008;Ochoa-Repáraz et al, 2009;Ichinohe et al, 2011;Janelsins et al, 2014;Benakis et al, 2016;Nakamura et al, 2016;Strzępa et al, 2017), and to reduce relative abundance of Th1 (Ochoa-Repáraz et al, 2009;Hill et al, 2010) and/or Th17 effector cells (Ivanov et al, 2008;Ochoa-Repáraz et al, 2009;Hill et al, 2010;Janelsins et al, 2014;Benakis et al, 2016). This shift in the balance between Tregs and effector T cells has been shown to reduce severity of multiple autoimmune (Ochoa-Repáraz et al, 2009;Benakis et al, 2016;Nakamura et al, 2016) and allergic diseases (Strzępa et al, 2017). On the other hand, the antibiotic-induced Treg promotion has been shown to prevent the development of proper immune responses to oral vaccination (Hall et al, 2008) and enteric infections (Sekirov and Finlay, 2009;Thackray et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…In line with the results from the current study, oral administration of broad-spectrum antibiotic cocktails is often reported to increase the relative abundance of CD4 + Treg cells in small intestine (Ivanov et al, 2008;Ochoa-Repáraz et al, 2009;Ichinohe et al, 2011;Janelsins et al, 2014;Benakis et al, 2016;Nakamura et al, 2016;Strzępa et al, 2017), and to reduce relative abundance of Th1 (Ochoa-Repáraz et al, 2009;Hill et al, 2010) and/or Th17 effector cells (Ivanov et al, 2008;Ochoa-Repáraz et al, 2009;Hill et al, 2010;Janelsins et al, 2014;Benakis et al, 2016). This shift in the balance between Tregs and effector T cells has been shown to reduce severity of multiple autoimmune (Ochoa-Repáraz et al, 2009;Benakis et al, 2016;Nakamura et al, 2016) and allergic diseases (Strzępa et al, 2017). On the other hand, the antibiotic-induced Treg promotion has been shown to prevent the development of proper immune responses to oral vaccination (Hall et al, 2008) and enteric infections (Sekirov and Finlay, 2009;Thackray et al, 2018).…”
Section: Discussionsupporting
confidence: 91%
“…Oral administration of enrofloxacin induced suppression of CHS and altered the gut microbiota composition in mice. Antibiotic treatment resulted in increased levels of Bacteroidetes, Bifidobacterium and Clostridium, while levels of segmented filamentous bacteria were decreased [25]. In our previous study, ciprofloxacin and metronidazole treatments blocked the suppressive activity of dietary SIs on CHS, whereas vancomycin treatment had little effect on their inhibitory activity against CHS [26].…”
Section: Discussionmentioning
confidence: 70%
“…It can be used to treat specific infections and against a broad spectrum of Gram-negative and Gram-positive bacteria in both stationary and growth phases of bacterial replication (Scheer, 1987). Its wide in vivo distribution, unique antimicrobial effect, high bioavailability, less toxicity, and side effects, make it one of the most commonly used antibiotics for treatment of various animal infectious diseases, and a desirable antibiotic choice for difficult-to-treat infections, particularly those that need long-term antibiotic treatment (Divers et al, 2008;Ebert et al, 2011;Reyes-Herrera et al, 2011;Jerjomiceva et al, 2014;Lin et al, 2014;Rico et al, 2014;Andrieu et al, 2015;Nguyen Dang Giang et al, 2015;Phillips et al, 2015;Piras et al, 2015;Carrascosa et al, 2017;Foster et al, 2017;Roth et al, 2017;Strze R pa et al, 2017;Zhu et al, 2017;Rico et al, 2018). The bactericidal activity of enrofloxacin is concentration-dependent, with susceptible bacterial cell death occurring within 20-30 minutes of exposure.…”
Section: Introductionmentioning
confidence: 99%